The impact of implementing Sustainable Urban Drainage Systems (SUDS) in a central neighborhood of a large city in Minas Gerais - Oliveira, Wevelton Ney Machado de; Silva , Jonathas Batista Gonçalves; Gomes, Maria Helena Rodrigues; Rocha, Cézar Henrique Barra; Pizzo, Henrique da Silva (National Journal of City Management, 2025)
Urban growth and soil sealing generate and intensify surface runoff processes, which overloads drainage systems and creates problems arising from rainfall events. The objective of the work was to analyze the effects of adopting sustainable urban drainage systems in the river basin of the Bom Pastor neighborhood in the city of Juiz de Fora, MG, by carrying out a study of the morphometric and rainfall characteristics of the region to determine the flow superficial at the outlet point. They were selected from the various drainage systems; the green roof, the micro-reservoir and the permeable pavement as being the most appropriate to the local reality. A comparison was made of the volume of surface runoff generated considering the current situation and after the implementation of drainage systems. A 21.23% reduction in surface runoff reaching the outlet point was achieved, through the reduction in the volume of runoff generated by the source. The aim is to contribute to the information generated in the region and encourage the implementation of these drainage systems in order to alleviate the problems caused by excessive local surface runoff.
Keywords: Urban drainage; Flooding; Sustainability